1. Question:উৎপাদকে বিশ্লেষণ কর: `4x^4 - 27x^2 - 81` 

    Answer
    `4x^4 - 27x^2 - 81`
    
      `= 4x^4 - 36x^2 + 9x^2 - 81`
    
      `= 4x^2(x^2 - 9) + 9(x^2 - 9)`
    
      `= (x^2 - 9) (4x^2 + 9)`
    
      `= (x^2 - 3^2) (4x^2 + 9)`
    
       `= (x + 3) (x - 3) (4x^2 + 9)`  (Ans)






    1. Report
  2. Question:উৎপাদকে বিশ্লেষণ কর: `ax^2 + (a^2 + 1) x + a` 

    Answer
    `ax^2 + (a^2 + 1) x + a`
    
      `= ax^2 + a^2x + x + a`
    
      `= ax(x + a) + 1(x + a)`
    
      `= (x + a) (ax + 1)`  (Ans)






    1. Report
  3. Question:উৎপাদকে বিশ্লেষণ কর: `3(a^2 + 2a)^2 - 22(a^2 + 2a) + 40` 

    Answer
    `3(a^2 + 2a)^2 - 22(a^2 + 2a) + 40`
    
      `= a^2 + 2a = p`
    
      `= 3p^2 - 22p + 40`
    
      `= 3p^2 - 12p - 10p + 40`
    
      `= 3p(p - 4) - 10(p - 4)`
    
      `= (p - 4) (3p - 10)`
    
      `= (a^2 + 2a - 4) {3(a^2 + 2a) - 10}`  [p]
    
      `= (a^2 + 2a - 4) (3a^2 + 6a - 10)`    (Ans)






    1. Report
  4. Question:উৎপাদকে বিশ্লেষণ কর: `14(x + z)^2 - 29(x + z) (x + 1) - 15(x + 1)^2` 

    Answer
    `14(x + z)^2 - 29(x + z) (x + 1) - 15(x + 1)^2`
    
       ধরি, `x + z = p`
    
       এবং `x + 1 = q`
    
      প্রদত্ত রাশি, 
         `= 14p^2 - 29pq - 15q^2`
    
         `= 14p^2 - 35pq + 6pq - 15q^2`
    
         `= 7p(2p - 5q) + 3q(2p - 5q)`
    
         `= (2p - 5q) (7p + 3q)`
    
         `= {2(x + z) - 5(x + 1)} {7(x + z) + 3(x + 1)}`
    
                                      [p, q এর মান বসিয়ে]
    
          `= (2x + 2z - 5x - 5) (7x + 7z + 3x + 3)`
    
          `= (2z - 3x - 5) (10x + 7z + 3)`  (Ans)






    1. Report
  5. Question:উৎপাদকে বিশ্লেষণ কর: `(a - 1)x^2 + a^2 xy + (a + 1) y^2` 

    Answer
    `(a - 1)x^2 + a^2 xy + (a + 1) y^2`
    
        `a - 1 = p`
    
         `a + 1 = q`
       ------------------------------
         :.` (a - 1) (a + 1) = pq`   [গুণ করে]
    
             `a^2 - 1 = pq`
    
            `:. a^2 = pq + 1`
    
      প্রদত্ত রাশি  
    
     `= px^2 + (pq + 1) xy + qy^2`
    
     `= px^2 + pqxy + xy + qy^2`
     
    `= px(x + qy) + y(x + qy)`
    
    `= (x + qy) (px + y)`
    
    `= {x + (a + 1)y} {(a - 1) x + y} `[p q এর মান বসিয়ে]
    
    `= (x + ay + y) (ax - x + y)`   (Ans)






    1. Report
Copyright © 2025. Powered by Intellect Software Ltd